Edukasi tentang Kehamilan Sehat Untuk Pencegahan Stunting di Desa Bahari 3, Kecamatan Sampolawa, Kabupaten Buton selatan - Hasriati, Wa ode; Yusuf, Sulfi A.; Jingsung, Julian; Afni, Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
WHO set a target for the stunting rate to be below 20%. the stunting rate in Indonesia fell from 24.4% in 2021 to 21.6% in 2022. One of the factors that can affect the growth of children, especially infants and toddlers, is the problem of good nutrition nutrition will increase children's intelligence, intelligence and skills, as well as the development and growth and development of mental psychology of children under five is inseparable from how the growth and development of children's brain cells. Stunting threatens a child's ability to learn, mental retardation and chronic diseases. At least 10 babies under five in Bahari Tiga Village experience stunting, 70% of mothers still do not understand the problem of stunting. Education was carried out to increase the knowledge of the Bahari Tiga Village community in the form of counseling at the Village Hall. The result was an increase in knowledge to 70% good knowledge. There is a need for training. skills in making complementary food for mothers who have toddlers, awareness of the head of the household to participate in fiber restrictions on the age of marriage supported by traditional leaders who allow the age of marriage> 19 years.